Analisa Bauran Pemasaran Terhadap Kepuasan Pelanggan (studi kasus pada usaha seblak) - Fitriani, Risa; Sitepu, Misya Vana; Amir, Twisca Putri Rahmah; Sari, Okta Permata; Yolanda, Feby (Universitas Medan Area, 2024)
The aim of this research is to determine the relationship between marketing output and customer satisfaction. Marketing and economic growth can be influenced by customer satisfaction. To solve this problem, the customer satisfaction of Seblak Aa Dadang and Seblak aa Dodi is focused. To solve this problem, the 4P method theory is used, which consists of product, place, price, and promotion. (promotion). Customer satisfaction is a dependent variable used to evaluate this method. Primary data, collected directly from research respondents and quantitatively analyzed, is used to collect data. The study involved 107 people who were clients of Aa Dadang and Aa Dodi. The study used Google Forms and SmartPLS 3.0. The research data was analyzed using measurement models and structural models. The results of this research show that products, prices, promotions, and locations have a significant and positive relationship with the purchasing decisions of Aa Dadang and Aa Dodi. This research can be used by Aa dadang and aa Dodi to build marketing strategies to customer satisfaction.